Optimization of TQFP molding process using neuro-fuzzy-GA approach - Chiang, TL; Su, CT (My University, 2003)
This paper focuses on an integated optimization problem that involves multiple qualitative and quantitative responses in the thin quad flat pack (TQFP) molding process. A fuzzy quality loss function (FQLF) is first applied to the qualitative responses., since the molding defects cannot be simply represented by the relationship between molding conditions and mathematical models. Neural network is then used to provide a nonlinear relationship between process parameters and responses. A genetic algorithm together with exponential desirability function is employed to determine the optimal parameter setting for TQFP encapsulation. The proposed method was implemented in a semiconductor assembly factory in Taiwan. The results from this study have proved the feasibility of the proposed approach. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: thin quad flat pack; fuzzy quality loss function; neural network; exponential desirability function; genetic algorithms